Experimental and computational analyses of the anti-alzheimer and antidiabetic effects of flavonoid-rich extract of avocado seeds (Persea americana Mill.) - Ojo, Oluwafemi Adeleke; Maduakolam-Aniobi, Tobiloba Christiana; Gyebi, Gideon Ampoma; Soyinka, Tenifayo Oluwatamilore; Ejiogu, Obianuju Favour; Ojo, Adebola Busola; Alruwaili, Mubarak; Ali, Naif H.; Alnaaim, Saud A.; Alsfouk, Bshra A.; Batiha, Gaber El-Saber (Springer Science and Business Media LLC, 2025)
Objectives
Our study examines the potential of flavonoid-rich extracts from avocado seeds (Persea americana) in combating Alzheimer’s disease and diabetes.
Methods
The antidiabetic activity of the extracts was assessed via the inhibition of α-amylase and α-glucosidase enzymes. Additionally, their anti-Alzheimer properties were evaluated through their anti-cholinesterase activities against AChE, BChE, and monoamine oxidase (MAO). Molecular docking and dynamics simulations were conducted to identify potential flavonoid inhibitors for the enzymes α-amylase, α-glucosidase, AChE, BChE, and monoamine oxidase.
Key findings
Notably, the extracts exhibited significant inhibitory activity against AChE (IC50 = 38.105 ± 0.32 µg/mL) and BChE (IC50 = 72.542 ± 1.470 µg/mL). MAO suppression protected against Fe2 + -mediated brain damage. Additionally, the flavonoid-rich extract of P. americana showed considerable inhibitory activity against α-amylase (IC50 = 608.516 ± 26.917 μg/mL) and α-glucosidase (IC50 = 790.570 ± 6.846 μg/mL) activities. HPLC–DAD profiling revealed the presence of gallic acid, caffeic acid, ferulic acid, rutin, p-coumaric acid, and quercetin. Molecular docking studies identified rutin, ferulic acid, and quercetin as the most promising ligands for the five protein targets investigated. Molecular simulations confirmed the stability of the protein‒ligand complexes, as evidenced by favorable thermodynamic parameters.
Conclusions
Overall, our findings revealed that P. americana seed extracts have promising anti-Alzheimer’s and antidiabetic effects.